An Analysis of Positive Politeness Strategies to Promote Effective Interaction in The Classroom - Nurmawti Nurmawati; Haryanto Atmowardoyo; Sukardi Weda (Hasanuddin University, 2019)
In the teaching learning process, a lively and friendly atmosphere in the classroom between teacher and students is the key to promote effective interaction. This study investigates an EFL classroom at the course in the terms of interaction between teacher and students to see how positive politeness strategies used by the teacher and the effect of positive politeness strategies in promoting effective interaction. One class of conversation class at the course was observed and recorded by the researcher. The recording were transcribed and analyzed by making use of related positive politeness strategies and effective interaction. Also, interview was done to get deeper data. The findings showed that positive politeness strategies existed in this class and it has created effective interaction between teacher and students and among the students.